Análisis del comportamiento del hormigón con agregado de fibra de vidrio y óxido de grafeno - Cruz España, Rony José (2025)
This research addresses the behavior of concrete with the incorporation of glass fiber and graphene oxide, aiming to improve its physical characteristics in comparison to traditional standards of strength and durability. Concrete is one of the traditionally used construction materials, although it has limitations in frequent applications such as cracking, fissuring, corrosion, and low tensile and compressive strengths, which jeopardize the stability and lifespan of infrastructures. It is highlighted that to reduce these limitations, new solutions must be explored through the incorporation of innovative materials such as graphene oxide and glass fiber. The objectives of this research are, on the one hand, to determine the physical characteristics of the modified concrete, and to compare the strength of the resulting concrete, in this case modified, with other conventional concretes. Additionally, it aims to establish the correct dosage of these materials, and finally to develop a mathematical model capable of describing the behavior. It is argued that the implementation of these new materials with concrete will improve its properties, increasing both its strength and durability. This research intends to contribute to the development of more resistant and sustainable construction materials, capable of meeting the needs of more demanding infrastructure projects, leading to the implementation of more advanced applications. The study aligns with research lines on advanced construction materials regarding the improvement of durability and structural performance.